Investigating the popularity of the main news bulletin on Muvi TV, a Zambian television station: a reception study of Lusaka viewers - Mbatha, Loisa (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2011)
The "tabloid TV" genre, like tabloid newspapers has been chastised for depoliticising the public by causing cynicism, and lowering the standards of rational public discourse. Such criticisms are not always based on a close interrogation of the reasons for the popularity of such a genre amongst its consumers. The "tabloid TV" news genre is a relatively new phenomenon in Zambia and in the African context in general. This study is an investigation of the rise in popularity of the Zambian television station, Muvi TV. It is a reception study of Lusaka (capital city) viewers, particularly the working class community, who make up the majority of the TV stations' audience. Members of this social group who have hitherto been marginalised from mainstream media discourses were interviewed. In particular, the study explores the meanings obtained from the content of Muvi TVs' tabloidised main evening news and its relevance to their everyday lived experiences. The TV station gives prominence to "micro-politics of everyday life", alongside "serious" stories albeit in a more lurid, sensationalised and personalised manner. In undertaking this investigation, the study draws primarily on qualitative in-depth interviews - focus group and individual. These techniques unearth the manner in which the viewers decode the messages and appropriate the meanings into their lived experiences. The study establishes that the popularity of Muvi TV is due to the emphasis on human-interest stories epitomised by tabloid journalism values. The working class majority is able to relate and identify with these stories, and attaches greater believability to the station's news as compared to the public broadcaster, the Zambia National Broadcasting Corporation (ZNBC). As such, Muvi TV can be seen to fulfil a political function despite its sensationalised approach.
Keywords: Television broadcasting of news -- Research -- Zambia; Broadcast journalism -- Research -- Zambia; Television programs -- Research -- Zambia